(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2021)
The antibacterial activity of the ethanol, and aqueous extracts from the fruit of A. marmelos was studied using disc diffusion method against five pathogenic bacterial strains, three Gram-positive bacteria (B. cereus, S. epidermidis, S. aureus) and two Gram-negative bacteria (E. aerogens, K. pneumoniae).The maximum 14.3mm zone of inhibitionwas observed at the concentration of 40mg/ml foraqueous extract. This may be due to the presence of the compounds Cuminaldehyde and Eugenol. In the case of ethanol, the maximum antibacterial activity was seen against E. aerogensfollowed by S. epidermidisand K. pneumonia. At the highest concentration of 160 mg/ml, it showed 18.3mm zone of inhibition. The antibiotic susceptibility showed that among all the bacterial strains S. aureuswas found more susceptible to ampicillin followed by K. pneumonia. Results suggest that the ethanolic extract has significant antibacterial activity against tested bacteria. The present study justifies the claimed uses of A. marmelos in the traditional system of medicine to treat various infectious diseases.